Sosialisasi Pelayanan Kesehatan Berbasis Digital Badan Penyelenggara Jaminan Sosial di Desa Sisarahiligamo Kecamatan Gunung Sitoli Kota Gunung Sitoli - Sulisna, Aida; Fauzi, Muhammad; Meliala, Sri Agustina (Jurnal Abdimas Jatibara, 2024)
The implementation of technology-based services issued by the Social Security Administering Body (BPJS) was established by the government with the aim of providing social protection and welfare for the entire community. The use of the JKN mobile application can provide several conveniences to the community and participants, namely ease of paying and changing membership data, convenience knowing information on family participant data, making it easy to find out information on participant contribution bills, making it easy to get information on Health Facilities and making it easy to submit complaints, as well as request information about JKN-KIS. Objective: to provide knowledge, training, and motivation to the public regarding digital-based health services from social security administering bodies. Method: presenting material and providing leaflets related to digital-based health services from social security administering bodies Results: Increased public understanding regarding Digital-Based Health Services of the Social Security Administering Agency. Community service activities carried out under the title Socialization of digital-based health services for social security providers in Sisarahiligamo village, Gunugsitoli sub-district, Gunungsitoli city, received good feedback from the community, especially the Sisarahiligamo community